2016
DOI: 10.1093/ijnp/pyw088
|View full text |Cite|
|
Sign up to set email alerts
|

BDNF-GSK-3β-β-Catenin Pathway in the mPFC Is Involved in Antidepressant-Like Effects ofMorinda officinalisOligosaccharides in Rats

Abstract: Background Morinda officinalis oligosaccharides have been reported to exert neuroprotective and antidepressant-like effects in the forced swim test in mice. However, the mechanisms that underlie the antidepressant-like effects of Morinda officinalis oligosaccharides are unclear.MethodsChronic unpredictable stress and forced swim test were used to explore the antidepressant-like effects of Morinda officinalis oligosaccharides and resilience to stress in rats. The phosphoinositide-3 kinase inhibitor LY294002 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 64 publications
(121 reference statements)
0
44
0
Order By: Relevance
“…MOOs have been reported to possess antidepressive and neurotrophic properties. 22,24,57 MOOs promote many beneficial processes including neuron survival, 24,58 and also increase protein level of monoamines, as well as BDNF in the hippocampus. 58 However, the antidepressive effect of MOOs in PSD models has not been tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOOs have been reported to possess antidepressive and neurotrophic properties. 22,24,57 MOOs promote many beneficial processes including neuron survival, 24,58 and also increase protein level of monoamines, as well as BDNF in the hippocampus. 58 However, the antidepressive effect of MOOs in PSD models has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that MOOs can upregulate monoamine levels in rodent depression models, as well as brain-derived neurotrophic factor (BDNF), which are all hallmarks of amelioration of depression. 20,22 MOOs have also been reported to enhance energy metabolism and inhibit neuronal apoptosis. 23,24 In this study, we found MOOs could ameliorate depressive-like behaviors and glucose metabolism in the medial prefrontal cortex (mPFC) of PSD rat models through upregulating GLUT3 expression, which ultimately enhanced the synaptic activity.…”
Section: Introductionmentioning
confidence: 99%
“…BDNF inhibits GSK3B activity by binding to TrKB to activate PI3K and Akt. 57 BDNF modulation may therefore be a mechanism by which GSK3B inhibitors like Lithium and sodium valproate ameliorate HIV-1 mediated neurotoxicity. 55…”
Section: Bdnf and Co-morbid Mental Health Disorders In Handmentioning
confidence: 99%
“…The protocols for sample preparation and Western blot were based on previous studies (Xu et al, 2017;Han et al, 2019). One day after the behavioral tests, the rats were decapitated and the brains were rapidly extracted and frozen in −60 • C N-hexane.…”
Section: Western Blot Assaymentioning
confidence: 99%